MODEL KOLABORASI KNOWLEDGE PADA KLASTER INDUSTRI KECIL DAN MENENGAH (Studi Kasus pada Klaster Rotan Trangsan, Gatak, Kab. Sukoharjo) - Usman Usman (JURNAL LITBANG PROVINSI JAWA TENGAH, 2009)
Modeling method in enterprise engineering has been much applied to integrate enterprises’s system, for intra as well as inter enterprises. Modeling method on many frameworks and methodology existing has focused on single enterprise manufacturer, so that it needs to be adjusted. The current research is intended to develop modeling method used to model knowledge collaboration on industry cluster based on HEMO modeling framework (Holonic Enterprise Modeling Ontology). Modeling analysis uses IDEF0, IDEF5 and FGD tools. To implement modeling method, it is chosen rattan cluster in Trangsan, Gatak, Sukoharjo. The research findings show that cluster concept or industry center can be approached by holon concept existing on HEMO modeling framework. HEMO modeling framework has been adjusted to be HEMO-Cluster and altogether with stance knowledge concept on knowledge management system can be used to model knowledge collaboration on industry cluster/center. The implementation result is able to depict knowledge collaboration through activity modeling on cluster. Modeling done gives a compass and media of documentation of collaboration so that tacit as well as explicit knowledge and other intangible activities on industry cluster/center can be identified and created, being documented, structured, easily traced, distributed and reused through documentation and discussion.